2021
DOI: 10.4103/cs.cs_225_20
|View full text |Cite
|
Sign up to set email alerts
|

Can Philanthropy Enable Collective Action to Conserve Rivers? Insights from a Decade of Collaboration in the Colorado River Basin

Abstract: Philanthropy plays an important but often invisible role in conserving rivers. We examine the influence of philanthropy on collective action and collaborative governance within the Colorado River Basin, a region where philanthropic support has been growing to achieve conservation objectives. Our short communication combines financial data, interviews, and documentary evidence to capture the opportunities and risks associated with philanthropy's increasing role. Financial expenditures are substantial, averaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This case provides additional evidence for the role foundations can play in facilitating collective action and highlights the need for more research on the opportunities and risks of philanthropy in collaborative governance (Gilson & Garrick, 2021). Some practitioners in Palau, for example, observed that coordination may have unintended consequences:…”
Section: Convening and Coordinationmentioning
confidence: 89%
See 1 more Smart Citation
“…This case provides additional evidence for the role foundations can play in facilitating collective action and highlights the need for more research on the opportunities and risks of philanthropy in collaborative governance (Gilson & Garrick, 2021). Some practitioners in Palau, for example, observed that coordination may have unintended consequences:…”
Section: Convening and Coordinationmentioning
confidence: 89%
“…Gilson & Garrick (2021, p. 190) argue that, while funding can enable collective action, “foundations should explicitly consider and address legacies of exclusion for marginalized actors and groups.” While recognizing the crucial role of Packard in bringing conservation actors together, the recent closure of the Western Pacific Program raises questions about the continued support and efficacy of coordination efforts, like FLMMA, as well as the impact of exits on established grantee networks (Le Cornu et al, in review).…”
Section: Packard's Governance Rolesmentioning
confidence: 99%
“…Landscape‐wide networks of funders and practitioners can lead to collective learning and large‐scale action (Gilson & Garrick, 2021). Funder networks built around specific topics can share learning, connect to new practitioners, and create pooled funding opportunities to amplify impact.…”
Section: Best Practices For Conservation Philanthropymentioning
confidence: 99%
“…), making it difficult for scholars and practitioners to find it, engage with it, and build on one another's work in a systematic way. Second, elite members of the philanthropic sector (e.g., high net‐worth individuals and foundations) are notoriously opaque, making empirical research on these actors a significant challenge—though creative scholars and a growing transparency movement are beginning to change that (Breeze, 2023; Gilson & Garrick, 2021).…”
mentioning
confidence: 99%
“…This special issue is motivated by these major changes. It showcases new research to help understand and inform the boom in conservation philanthropy in the oceans (Gruby et al, 2021), on land (Opel & Titze, 2022; Waldron et al, 2013), and relating to freshwater (Gilson & Garrick, 2021). In so doing, it seeks to define and nurture the nascent field of research in conservation philanthropy.…”
mentioning
confidence: 99%